Bromide-assisted catalytic oxidation of lead(ii) solids by chlorine in drinking water distribution systems. Issue 62 (19th July 2017) - Orta, John; Patton, Samuel; Liu, Haizhou
Abstract : This study investigated the effect of bromide on the oxidation of three lead(ii ) solids by chlorine – a redox process critical to the control of lead release in drinking water distribution systems. Abstract : This study investigated the effect of bromide on the oxidation of three lead(ii ) solids by chlorine – a redox process critical to the control of lead release in drinking water distribution systems. Bromide had a strong catalytic effect on the oxidation of lead(ii ) carbonate solids, but had a limited impact on the oxidation of lead(ii ) phosphate.